SMART MARKETING TRANSFORMATION STRATEGY BRANCH AT BANK MANDIRI REGIONAL II PALEMBANG - Muhammad Fadhil Amrullah; Juhaini Alie (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
The purpose of this study is to analyze, prove marketing transformation strategies, and find out the factors that become obstacles in the implementation of transformation strategies in smart branches at bank mandiri regional II Palembang. The research method used in this study is qualitative method. This type of research is a case study with a single case study design. In this study using a descriptive research design. The smart branch marketing transformation strategy at Bank Mandiri Regional II Palembang has been quite effectively implemented, this digital banking 5.0 innovation by Mandiri offers a different experience from other banking services because the ease, speed and accountalization of solving customer needs is very structured and measurable in accordance with customer needs. The type of research in this research is a case study with a single case study design. In this study using a descriptive research design. The smart branch marketing transformation strategy at Bank Mandiri Regional II Palembang has been quite effectively implemented, this digital banking 5.0 innovation by Mandiri offers a different experience from other banking services because the ease, speed and accountalization of solving customer needs is very structured and measurable in accordance with customer needs.